Bahasa Inggris - Yadano, Putri Sri Widya; Adnan Malaha; Astria lolo (LPPM Universitas Bina Mandiri Gorontalo, 2023)
This study aims to identify the presence or absence of borax and formalin in meatballs and wet noodles in Gorontalo City. The type of research used in this research is descriptive with a qualitative approach. Using the curcumin paper method (tumeric) to identify the borax content and the 0.1 N KMnO4 method (Potassium Permanganate) to identify the Formalin content. The sampling technique is purposive sampling and the data collection technique is based on the results of tests conducted in the laboratory. The data processing method goes through several stages, namely editing, coding, tabulating, data cleaning, data descrbing and data analysis, namely the number of presentation frequencies is calculated using the number formula for each sample of meatballs and wet noodles that are positive for borax and formalin divided by the total number of each sample of meatballs and wet noodles.The results of the research carried out can be concluded from the total sample of meatballs, namely 20 samples, 20 were negative Borax (0%) and 16 of them were Formalin positive (80%). while for the sample of wet noodles with a sample of 7, 6 positive results were obtained for Borax (85.71%) and 5 were positive for Foramalin (71.42%).